The importance of soft skills for leaders / Siti Asiah Md Shahid - Md Shahid, Siti Asiah (2012)
This article addresses the importance for leaders in developing their personal and interpersonal soft skills, which are critical for organization success. Paradoxically, many leaders prefer hard skills over soft skills because they believe that hard, strategic, and analytical skills are required for effective management and leadership.Leading others in turbulent times requires leaders to provide effective leadership to the organization's people, focusing on both results as well relationships. In addition, the shift in the workplace from manufacturing or production work to service or knowledge work has brought about changes in the nature of job performance. Jobs in the service sector are characterized by interpersonal and face-to-face interactions with employees, customers, or clients. Therefore, interpersonal skills have become more crucial to effective leadership. Hence, it is recommended that more emphasis be placed on identifying and developing leaders with soft skills. For this reason, significant ongoing investments in education and training are needed in the changing face of organizations. Therefore, organizations must be willing to commit the time necessary for soft skills to take hold, as people are the key to an organization's success. On the issue of leadership, it is obvious that successful leaders are those with highly developed soft skills.